2014
DOI: 10.1051/0004-6361/201424131
|View full text |Cite
|
Sign up to set email alerts
|

High speed magnetized flows in the quiet Sun

Abstract: Context. We analyzed spectropolarimetric data recorded with Hinode/SP in quiet-Sun regions located at the disk center. We found single-lobed Stokes V profiles showing highly blue-and red-shifted signals. Oftentimes both types of events appear to be related to each other. Aims. We aim to set constraints on the nature and physical causes of these highly Doppler-shifted signals, as well as to study their spatial distribution, spectropolarimetric properties, size, and rate of occurrence. Also, we plan to retrieve … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 46 publications
(62 reference statements)
0
9
0
Order By: Relevance
“…Therefore, as pointed out by Bellot Rubio (2009), the physical mechanism behind the satellite lobes seems to be unrelated to any magnetic field configuration. This property indicates that they cannot be associated to the events studied in (Quintero Noda et al 2014a), discarding the possibility that these horizontal flows were the connection between the opposite footpoints analysed in the cited work. We estimate the density of events taking into account how many pixels of the observed map fulfils the threshold criteria imposed, see Section 2.2.…”
Section: Detection Of Eventsmentioning
confidence: 91%
See 1 more Smart Citation
“…Therefore, as pointed out by Bellot Rubio (2009), the physical mechanism behind the satellite lobes seems to be unrelated to any magnetic field configuration. This property indicates that they cannot be associated to the events studied in (Quintero Noda et al 2014a), discarding the possibility that these horizontal flows were the connection between the opposite footpoints analysed in the cited work. We estimate the density of events taking into account how many pixels of the observed map fulfils the threshold criteria imposed, see Section 2.2.…”
Section: Detection Of Eventsmentioning
confidence: 91%
“…These high speed velocities are usually translated into characteristic spectral features. From highly dopplershifted circular polarization signals with complex profile shapes as single-lobed (Borrero et al 2010;Quintero Noda et al 2014a;Jafarzadeh et al 2015) or multi-lobed profiles (Shimizu et al 2008a;Quintero Noda et al 2014b) to secondary satellite lobes in the intensity profiles (Bellot Rubio 2009). The reason behind this high speed plasma is still under debate and it seems that there is not a single answer.…”
Section: Introductionmentioning
confidence: 99%
“…We take advantage of the knowledge acquired in Quintero Noda et al (2014a) andQuintero Noda et al (2015) to determine this maximum number of nodes. We allowed seven nodes for the temperature T(τ), five for the line of sight (LOS) component of the velocity v los (τ), five for the magnetic field strength B(τ), three for the inclination of the magnetic field γ(τ), and two for the azimuthal angle of the magnetic field φ (τ).…”
Section: Configurationmentioning
confidence: 99%
“…These events were explained in terms of magnetic reconnection, where freshly emerged flux tubes within granules interact with pre-existing fields in intergranular areas (Borrero et al 2013;Quintero Noda et al 2013). Quintero Noda et al (2014) found that the extremely blueshifted events, observed by Hinode/SP, are often accompanied by redshifted Stokes V signals. Together, they represent footpoints of magnetic Ωloops with flows along them.…”
Section: Introductionmentioning
confidence: 99%
“…Together, they represent footpoints of magnetic Ωloops with flows along them. Quintero Noda et al (2014) argued that the siphon flow mechanism (Montesinos & Thomas 1993) was the only explanation for those flow motions along the arched magnetic flux tubes.…”
Section: Introductionmentioning
confidence: 99%